Tracheids of the Jurassic sediments of Ukraine - Shevchuk, O.А. (Reports of the National Academy of Sciences of Ukraine, 2015)
For the first time in Jurassic sediments in Ukraine, the microscopic pieces of wood tracheids, installed in the sediments of the Bajocian, Bathonian, Callovian, and Tithonian ages are revealed on outcrops and in wells: Ukrainian Shield, the Dnieper-Donets basin and the Crimean Mountains. The comparative anatomical analysis of fragments of coniferous wood of the Jurassic in Ukraine is made, and their characteristics and the age range are established. The phototables, which depict fragments of Jurassic wood, are presented.